(untitled) (Intent Research Scientific Journal, 2023)
The life of bees is an extremely complex family, and each individual performs a specific task. Therefore, in the family there is a mother bee that gives birth, a sterile female bee, that is, a worker bee, and male bees (truten), which differ from each other in terms of their structure and physiological characteristics. This is called polymorphism. Polymorphism usually arises from the fact that each individual performs a certain task in the family, that is, the distribution of the work performed is directly related to their morphological difference. In the middle of the summer season, there are 60-70,000 bees in the family of strong bees bred in apiaries, and 80-90,000 bees in the hybrid bee family. Due to the large number of worker bees in the family, they can collect enough food for the next year’s sap transport period in a short time, that is, in 20-30 days. As a result of a large number of bees living in a community, bees keep the necessary environment and heat around them during the cold winter days.